2020
DOI: 10.3390/jmse8110854
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Small Phytoplankton Communities to the Total Dissolved Inorganic Nitrogen Assimilation Rates in the East/Japan Sea: An Experimental Evaluation

Abstract: As a part of Korean-Russian joint expeditions in the East/Japan Sea during 2012 and 2015, a set of total and small (<2 μm) phytoplankton NO3− and NH4+ uptake rate estimations were carried out. The study aimed to assess the spatio-temporal variations in dissolved inorganic nitrogen (DIN) assimilation by the total and small phytoplankton. The results show that the total NO3− uptake rates during 2012 varied between 0.001 and 0.150 μmol NL−1h−1 (mean ± SD = 0.034 ± 0.033) and that the total NH4+ uptake rates ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…High concentrations of TN made the zooplankton community more stable (Figure 10C). Bhavya et al (2020)have shown that the total uptake of nitrogen by phytoplankton is in the range of 10.24-59.36% and 30.21-68.55%. Therefore, high concentration of TN promotes the reproduction of phytoplankton (Liu et al, 2022).…”
Section: Environmental Factorsmentioning
confidence: 99%
“…High concentrations of TN made the zooplankton community more stable (Figure 10C). Bhavya et al (2020)have shown that the total uptake of nitrogen by phytoplankton is in the range of 10.24-59.36% and 30.21-68.55%. Therefore, high concentration of TN promotes the reproduction of phytoplankton (Liu et al, 2022).…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Marine phytoplankton are an important indicator of marine ecosystem changes in response to climate-induced environmental change [2,[4][5][6], since they are major primary producers that consolidate solar energy into organic matter and transfer it to marine ecosystems throughout the food web. Recently, increasing numbers of roles of small phytoplankton as a major contributor to primary production have been reported in various oceans, and it has been found that small phytoplankton could become more prominent under an ocean warming scenario [2,4,[6][7][8][9]. The ecological and biogeochemical traits of small phytoplankton are very different from those of large phytoplankton [3,4,9].…”
Section: Marine Nitrogen Fixation and Phytoplankton Ecologymentioning
confidence: 99%
“…Recently, increasing numbers of roles of small phytoplankton as a major contributor to primary production have been reported in various oceans, and it has been found that small phytoplankton could become more prominent under an ocean warming scenario [2,4,[6][7][8][9]. The ecological and biogeochemical traits of small phytoplankton are very different from those of large phytoplankton [3,4,9]. Therefore, it is urgent to verify the different biological and chemical properties of small phytoplankton and understand their ecological roles under ongoing environmental changes.…”
Section: Marine Nitrogen Fixation and Phytoplankton Ecologymentioning
confidence: 99%
“…Recently, primary productivity in Korean waters has exhibited a rapidly decreasing trend, with phytoplankton miniaturization purported to be the primary contributing factor [17][18][19]. Indeed, small phytoplankton play an important role in primary productivity and the marine ecosystem food web [18,[20][21][22][23]. However, past research on phytoplankton in the South Sea has primarily focused on the coastal region, with relatively limited studies reporting the phytoplankton community structure during specific periods in the nearshore areas [11,[24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%